Comprehension of object relatives in Spanish: the role of frequency and transparency in acquisition and adult grammar - Llompart, Miquel; Fernández Santos, Sara; Dabrowska, Ewa (Cognitive Linguistics, 2024)
This study investigates the relative roles of frequency and transparency in native speakers’ comprehension of Spanish object relative sentences by comparing performance with two variants of the construction that differ in these properties. Experiment 1 suggests that seven- to eight-year-old children’s processing of object relative sentences is consistently facilitated by variant frequency and likely relies on separate representations for each variant as two different, although related constructions. Experiment 2 turns to adult comprehension of the two variants, showing similar accuracy and reaction time patterns for both variants for this population. This second outcome could be interpreted as a decrease in frequency effects over time, in line with the power law of practice, as an experience-based increase in the ability to make use of redundant markers, or both.<br
CRIS-Team Scopus Importer:2024-11-01
Keywords: relative clauses; Spanish; first language acquisition; object relatives; Construction Grammar